Beetles (Coleoptera) of Peru: A Survey of the Families. Tenebrionidae - Smith, Aaron D. (2015)
A survey of the diversity in Peru of the family Tenebrionidae is presented, including a list of 353 species/subspeciesarranged in 8 subfamilies, 37 tribes, and 105 genera. A discussion on geographic distribution and habitats of the genera are presented, founding that some genera inhabit the coastal deserts of western Peru, others are found in the Andes, including the Western Andean range, and the remaining in Amazonia, including the Eastern Andean range. Five species previously listed in catalogs as occurring in Peru wereexcluded from the checklist, in which are highlighted the new records and endemic species for the country.